1998
DOI: 10.1002/(sici)1096-9136(1998110)15:11<937::aid-dia701>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of fasting glycaemia by intravenous GLP-1 ([7-36 amide] or [7-37]) in Type 2 diabetic patients

Abstract: Intravenous GLP-1 [7-36 amide] can normalize fasting hyperglycaemia in Type 2 diabetic patients. Whether GLP-1 [7-37] has similar effects and how quickly plasma glucose concentrations revert to hyperglycaemia after stopping GLP-1 is not known. Therefore, 8 patients with Type 2 diabetes (5 female, 3 male; 65+/-6 years; BMI 34.3+/-7.9 kg m(-2); HbA1c 9.6+/-1.2%; treatment with diet alone (n=2), sulphonylurea (n=5), metformin (n=1)) were examined twice in randomized order. GLP-1 [7-36 amide] or [7-37] (1 pmol kg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 32 publications
(52 reference statements)
4
26
0
Order By: Relevance
“…When administered by intravenous infusion to type 2 diabetic subjects, GLP-1 stimulates pancreatic insulin secretion and blunts the postprandial hyperglycemic excursion that is typically observed following ingestion of a meal [10][11][12]. Short term or continuous infusion of GLP-1 restores fasting glycemia in type 2 diabetic subjects [13][14][15][16][17][18][19], and available evidence indicates that GLP-1 remains an effective blood glucose lowering agent under conditions in which subjects are not responsive to administered sulfonylureas such as tolbutamide, glyburide, or glipizide [20][21][22]. Antidiabetogenic actions of GLP-1 in type 2 diabetic subjects are manifest as an improvement of pancreatic b-cell function, as measured by a clear restoration of the missing first phase component of glucose-dependent insulin secretion [10,15,19,23].…”
Section: B Glp-1 As a Blood Glucose-lowering Agentsupporting
confidence: 89%
“…When administered by intravenous infusion to type 2 diabetic subjects, GLP-1 stimulates pancreatic insulin secretion and blunts the postprandial hyperglycemic excursion that is typically observed following ingestion of a meal [10][11][12]. Short term or continuous infusion of GLP-1 restores fasting glycemia in type 2 diabetic subjects [13][14][15][16][17][18][19], and available evidence indicates that GLP-1 remains an effective blood glucose lowering agent under conditions in which subjects are not responsive to administered sulfonylureas such as tolbutamide, glyburide, or glipizide [20][21][22]. Antidiabetogenic actions of GLP-1 in type 2 diabetic subjects are manifest as an improvement of pancreatic b-cell function, as measured by a clear restoration of the missing first phase component of glucose-dependent insulin secretion [10,15,19,23].…”
Section: B Glp-1 As a Blood Glucose-lowering Agentsupporting
confidence: 89%
“…incretin hormones; diabetes; animal models; glucagon-like peptide-1 GLUCAGON-LIKE PEPTIDE-1 (GLP-1), an incretin hormone secreted from the intestinal L cells (23,16), is highly effective in lowering blood glucose in type 2 diabetic patients (12,21,22,28). The antihyperglycemic effects of GLP-1 are multifactorial, involving the pancreas, gastrointestinal tract, and brain.…”
supporting
confidence: 89%
“…Another conceivable explanation is that the contribution of endogenous incretin may increase with aging, but its physiological bioactivity would be very low because of the fast degradation by plasma DPP-IV (9, 10). Consistent with this hypothesis, recent clinical studies have demonstrated that intravenous administration of GLP-1 improved the fasting hyperglycemia and islet dysfunction in elderly patients (65-to 74-year-old) with Type 2 diabetes (29,30). In addition, our study demonstrated that the DPP-IV inhibitor NVP-DPP728 improved glucose tolerance in aged rats by inhibiting plasma DPP-IV activity, presumably in association with the endogenous incretin bioactivity.…”
Section: Discussionmentioning
confidence: 99%